Paired protein kinases PRKCI-RIPK2 promote pancreatic cancer growth and metastasis via enhancing NF-κB/JNK/ERK phosphorylation - Juying Jiao; Linjie Ruan; Chien-shan Cheng; Fengjiao Wang; Peiwen Yang; Zhen Chen (BMC, 2023)
Abstract Background Protein kinases play a pivotal role in the malignant evolution of pancreatic cancer (PC) through mediating phosphorylation. Many kinase inhibitors have been developed and translated into clinical use, while the complex pathology of PC confounds their clinical efficacy and warrants the discovery of more effective therapeutic targets. Methods Here, we used the Gene Expression Omnibus (GEO) database and protein kinase datasets to map the PC-related protein kinase-encoding genes. Then, applying Gene Expression and Profiling Interactive Analysis (GEPIA), GEO and Human Protein Atlas, we evaluated gene correlation, gene expression at protein and mRNA levels, as well as survival significance. In addition, we performed protein kinase RIPK2 knockout and overexpression to observe effects of its expression on PC cell proliferation, migration and invasion in vitro, as well as cell apoptosis, reactive oxygen species (ROS) production and autophagy. We established PC subcutaneous xenograft and liver metastasis models to investigate the effects of RIPK2 knockout on PC growth and metastasis. Co-immunoprecipitation and immunofluorescence were utilized to explore the interaction between protein kinases RIPK2 and PRKCI. Polymerase chain reaction and immunoblotting were used to evaluate gene expression and protein phosphorylation level. Results We found fourteen kinases aberrantly expressed in human PC and nine kinases with prognosis significance. Among them, RIPK2 with both serine/threonine and tyrosine activities were validated to promote PC cells proliferation, migration and invasion. RIPK2 knockout could inhibit subcutaneous tumor growth and liver metastasis of PC. In addition, RIPK2 knockout suppressed autophagosome formation, increased ROS production and PC cell apoptosis. Importantly, another oncogenic kinase PRKCI could interact with RIPK2 to enhance the phosphorylation of downstream NF-κB, JNK and ERK. Conclusion Paired protein kinases PRKCI-RIPK2 with multiple phosphorylation activities represent a new pathological mechanism in PC and could provide potential targets for PC therapy.